Diacetylamethystoidin A protects isolated working rat heart against myocardial reperfusion injury - Zhang Chun-Fen; Wang Dao-Sheng; Ling Xiu-Zhen (Acta Pharmacologica Sinica; Vol 17, No 3 (May 1996): Acta Pharmacologica Sinica, 2016)
AIM: To observe the effect of diacetylamethystoidin A (6 alpha, 13 beta-diacetyl-11, 15-dioxo-19-hydroxyl-kaurene, DAA-A) on myocardial ischemia reperfusion injury. METHODS: Working heart mode was induced in isolated rat heart subjected to a 40-min ceasing perfusion followed by a 25-min reperfusion. RESULTS: DAA-A 0.13, 0.25, 0.50 mmol.L-1 reduced the incidence of ventricular fibrillation (1, 1, 0 vs 4 in Vehicle and 5 in Control, respectively), increased the coronary flow (mL.min-1, 1.8 +/- 0.9, 1.9 +/- 0.8, 1.7 +/- 0.6 vs 1.0 +/- 0.3 in Vehicle and 0.9 +/- 0.5 in Control as reperfusion time 5 min, respectively), improved the contractile function of heart, decreased the release of lactic dehydrogenase (LDH) and malondialdehyde (MDA). DAA-A 0.25 mmol.L-1 reduced the injury of myocardial cell ultrastructure. CONCLUSION: DAA-A has cardioprotective effect through diminishing cellular lipid peroxidation induced by oxygen free radicals.